2017
DOI: 10.1177/1479972316674413
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of volume recruitment–derecruitment manoeuvre on chest-wall motion in Duchenne muscular dystrophy

Abstract: Because progressive respiratory muscle weakness leads to decreased chest-wall motion with eventual ribcage stiffening, the purpose was to compare vital capacity (VC) and contributions of chest-wall compartments before and after volume recruitment-derecruitment manoeuvres (VRDM) in Duchenne muscular dystrophy (DMD). We studied nine patients with DMD and VC lower than 30% of predicted. VRDM was performed using 15 insufflations-exsufflations of þ30 to À30 cmH 2 O. VC and three-dimensional chest-wall motion were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…These findings are consistent with a recent study assessing the effects of volume recruitment-derecruitment maneuvers performed by means of MI-E on 9 subjects with DMD. 15 The acute reduction of the breathing frequency after MI-E may have different origins because it is complexly regulated by the respiratory center in the medulla and pons of the brainstem through various inputs. These include signals from the peripheral chemoreceptors and central chemoreceptors, from the vagus nerve and glossopharyngeal nerve carrying input from stretch receptors and other mechanoreceptors in the lungs, bronchi, and bronchioles, as well as signals from the cerebral cortex and hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with a recent study assessing the effects of volume recruitment-derecruitment maneuvers performed by means of MI-E on 9 subjects with DMD. 15 The acute reduction of the breathing frequency after MI-E may have different origins because it is complexly regulated by the respiratory center in the medulla and pons of the brainstem through various inputs. These include signals from the peripheral chemoreceptors and central chemoreceptors, from the vagus nerve and glossopharyngeal nerve carrying input from stretch receptors and other mechanoreceptors in the lungs, bronchi, and bronchioles, as well as signals from the cerebral cortex and hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, optoelectronic plethysmography (OEP) is particularly suitable because it allows a detailed analysis of thoraco-abdominal kinematics and permits study of the action of different respiratory muscle groups. This technique is particularly useful in patients with DMD because it allows identification of variations in end-expiratory volumes, breathing pattern, vital capacity, and cough associated with the progression and disease severity; [12][13][14] OEP can be performed without requiring a mouthpiece or mask, which means it can be used during MI-E. 15 Nevertheless, a specific validation of OEP use in patients with DMD is lacking in the literature, so we also compared the volume variations during vital capacity maneuvers and cough peak flow (CPF) as measured simultaneously with a portable spirometer and with OEP.…”
Section: See the Related Editorial On Page 1076mentioning
confidence: 99%
“…Peak expiratory flow was increased during LVR but not unassisted peak expiratory flow 40 . Another adult study by Meric et al 23 demonstrated positive effect on chest-wall motion asymmetry and a small but significant increase of vital capacity. The vital capacity return to baseline within one hour and the shallow breathing index increased significantly.…”
Section: Discussionmentioning
confidence: 92%
“…No changes in lung-volume recruitment or unassisted cough peak flow could be demonstrated 22 . Another study in a small group of adult subjects with DMD demonstrated a short-lasting positive effect on chest-wall motion asymmetry and a small but significant increase of vital capacity 23 .We therefore aimed to quantitatively and qualitatively describe the short-term effect of the insufflation/exsufflation manoeuvres on ventilation distribution and other lung function parameters in subjects with NMD. We hypothesised that an insufflation/exsufflation treatment session leads to short-term changes in ventilation inhomogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Other research using LVR, an MI-E device or mouthpiece NIV to deliver assisted inflation therapy has likewise demonstrated no10 37 or little9 38 effect on VC and/or unassisted PCF. In a study of nine participants with DMD, MI-E produced a statistically significant increase in VC immediately post-therapy that dissipated by 1 hour,38 however, the mean improvement of 8% is within the error of this measurement13 and may not be clinically important.…”
Section: Discussionmentioning
confidence: 99%